The Influence of Split and Skipping Exercises on the Speed of Dollyo Chagi Kicks in Tae Kwon Do Martial Arts Athletes - Putri, Aneta Dwi Rahma; Mushofi, Yuskhil; Afandi, Achmad; Artanty, Ary; Aris, Tria Muhammad; Budiono, Dwi (JUMORA: Jurnal Moderasi Olahraga, 2025)
The purpose of this study is to determine the extent of the effect of split and skipping training on the speed of Dollyo Chagi kicks in Taekwondo martial arts athletes at the Dojang of SMP PGRI 1 Wajak. This research is an experimental study. The method used involves split and skipping training. The participants in this study were 30 Taekwondo athletes from the Dojang of SMP PGRI 1 Wajak, Malang. The research variable is the speed of the Dollyo Chagi kick in Taekwondo athletes at the same Dojang. Data were collected through treatment-based training sessions with specific instructions. The data analysis included a normality test and a homogeneity test. The normality test showed that the data were normally distributed, allowing the treatment to proceed, while the homogeneity test results indicated that the data were homogeneous. Based on the results, it can be concluded that the t-test value for experimental group 1 (3.760) is greater than the t-table value (2.145), indicating that the alternative hypothesis is accepted. This means that split training has a significant effect on the speed of the Dollyo Chagi kick in Taekwondo athletes at SMP PGRI 1 Wajak. Similarly, the t-test value for experimental group 2 (3.720) is greater than the t-table value (2.145), thus accepting the alternative hypothesis. This indicates that skipping training also has a significant effect on the speed of the Dollyo Chagi kick in the same group of athletes. Based on the data analysis, there was a significant improvement in the experimental groups. The treatment, which was conducted over 12 sessions with a frequency of 3 times per week, contributed to the improvement in Dollyo Chagi kick speed